THE EFFECT OF ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL CLIMATE ON EMPLOYEE PERFORMANCE IN MINISTRY OF COMMUNICATION AND INFORMATICS JAKARTA - Violita, Vivi (International Humanities and Applied Science Journal, 2020)
ABSTRACT - This study aims to examine and analyze the effect of organizational commitment and organizational climate on employee performance. The object of this research is the part of staffing in communication and informatics institutions located in Jakarta. This study was conducted on 30 respondents with this researcher using the sample method: saturated or biased is also called the census method and the data obtained is analyzed using PLS (Partial Least Square) analysis techniques through SmartPLS software. The results is organizational commitment has positive and significant effect on employee performance, and organizational climate has negative and insignificant effect on employee performance.Keywords: organizational commitment; organizational climate; employee performance